Species Identification of Larval Fish in Hawaiian Waters Using DNA Barcoding - Xing, Bingpeng; Wang, Chunguang; Wu, Qiong; Wang, Yanguo; Chen, Xiaoyin; Sun, Rouxin; Zhang, Zhilan; Xiang, Peng (Frontiers in Marine Science, 2022)
Taxonomic information is important to fisheries management and conservation. In this study, we collected 95 specimens of larval fish from Hawaiian waters and a total of 92 mitochondrial COI barcode sequences were obtained, representing 20 species, 18 genera and 12 families. The determined average Kimura-2-parameter distances within species, genera, families, and orders were 0.72%, 25.99%, 26.30%, and 27.50%, respectively, and the mean interspecific distance was found to be 36-fold higher than the mean intraspecific distance. Phylogenetic tree analysis showed that individuals belonging to the same species were clustered together and could be clearly distinguished. The findings of this study can make a valuable contribution to our knowledge of the diversity and dispersal of larval fish in Hawaiian waters.